1997
DOI: 10.1016/s0022-5347(01)68171-0
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy in the Octogenarian

Abstract: The results of this study support the use of cystectomy in octogenarians with invasive bladder cancer. Surgery can be accomplished with acceptable morbidity and mortality. Radical cystectomy in this population offers the best opportunity for sustained disease-free quality survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 18 publications
5
61
1
6
Order By: Relevance
“…Studies of patients aged > 70 years found the mean hospital stay after RC to be 11-28 days [3,15]. In addition, patients aged > 79 years were found to be re-admitted to the hospital 66% of the time within 6 months of RC, for either medical or surgical complications [16]. A long hospital stay combined with recovery of function after the hospitalization can be a significant proportion of an elderly patient's remaining life, and should be factored into the decision to proceed with RC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients aged > 70 years found the mean hospital stay after RC to be 11-28 days [3,15]. In addition, patients aged > 79 years were found to be re-admitted to the hospital 66% of the time within 6 months of RC, for either medical or surgical complications [16]. A long hospital stay combined with recovery of function after the hospitalization can be a significant proportion of an elderly patient's remaining life, and should be factored into the decision to proceed with RC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several centers specifically evaluating RC in the elderly have concluded that RC may be performed with a higher but acceptable morbidity rate 7,8,17,18 .…”
Section: Resultsmentioning
confidence: 99%
“…While several centers have concluded that RC may be performed with a higher but acceptable morbidity rate [6][7][8] , its role in elderly patients is still in debate due to the associate morbidity.…”
Section: Muscle Invasive Bladder Cancer (Mibc) Accounts Formentioning
confidence: 99%
“…The mortality rate of urinary diversion by an ileal conduit or neobladder reconstruction was 0-4.5% in varied studies which is similar to the present study using CU of urinary diversion with no mortality. [20][21][22][23][24][25][26][27] It is an observational, retrospective study and the sample size is small.…”
Section: Discussionmentioning
confidence: 99%